Формування бази знань системи підтримки прийняття рішень визначення стану багатозв’язного об’єкту - Тімофєєв, В. О.; Хрустальова, С. В. (ХНУРЕ, 2019)
The proposed to determine the knowledge base of decision support system definition and prediction of the state of multi-connected object, which is represented by the production rules obtained using the method of Data Mining, which allowed to establish the dependencies in the accumulated data and write the rules of inference that are used in the software solution. This data depends on the adequacy and value of the recommendations, the object under study and the performance of the system